The Effect of Financial Literacy on Consumptive Behavior of Economics Education Students of the Faculty of Economics Universitas Negeri Makassar - Nurhayani Nurhayani; Nurwahida Nurwahida; Satria Ramli (Journal of Economics, Entrepreneurship, Management Business and Accounting, 2023)
This study aims to describe and test the effect of financial literacy on consumptive behavior in students of the Faculty of Economics, Makassar State University. This study was designed using a quantitative approach using SPSS. The population of this study were all students of the Faculty of Economics, Makassar State University who had passed general courses as many as 541 students. The sample of this research was 230 students using proportional random sampling. Collecting data in this study using SEM (Structural Equation Modeling) analysis. Based on the results of the research conducted, it is known that there is a significant influence between financial literacy on consumptive behavior in students of the Faculty of Economics, Makassar State University.